2019
DOI: 10.1111/jgs.15861
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Safety: Risk of Mortality and Cardiovascular Events in Nursing Home Residents, a Prospective Study

Abstract: BACKGROUND Acetaminophen is the most widely used analgesic today. A recent systematic review found increased adverse events and mortality at therapeutic dosage. Our aim was to challenge these results in a large sample of older adults living in nursing homes (NHs). DESIGN Prospective study using data from the Impact of Educational and Professional Supportive Interventions on Nursing Home Quality Indicators project (IQUARE), a multicenter, individually tailored, nonrandomized controlled trial in NHs across south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
14
0
2
Order By: Relevance
“…That paracetamol had statistically significant benefits for pain and physical function (despite not achieving MCID thresholds; see the online supplementary table 1), coupled with its good harms profile indicate the drug should not be jettisoned as one of the first-line treatments for managing pain in the management of OA. Indeed, a recent large prospective study of elderly subjects (n=5429) concluded that ‘despite polypharmacy and polymorbidity’, acetaminophen (paracetamol) remains a first-line analgesic for managing pain 7…”
Section: Statistically Significant Benefit Versus Clinical Importancementioning
confidence: 99%
“…That paracetamol had statistically significant benefits for pain and physical function (despite not achieving MCID thresholds; see the online supplementary table 1), coupled with its good harms profile indicate the drug should not be jettisoned as one of the first-line treatments for managing pain in the management of OA. Indeed, a recent large prospective study of elderly subjects (n=5429) concluded that ‘despite polypharmacy and polymorbidity’, acetaminophen (paracetamol) remains a first-line analgesic for managing pain 7…”
Section: Statistically Significant Benefit Versus Clinical Importancementioning
confidence: 99%
“…Интересные данные приводят Р. Girard и соавт. [30], которые исследовали влияние приема ПАР на риск кардиоваскулярных катастроф у 5429 пожилых французов (средний возраст 86,1±8,1 года), нуждавшихся в уходе на дому. Из них 2239 регулярно принимали ПАР.…”
Section: парацетамолunclassified
“…Recently, Roberts et al conducted a meta‐analysis that found that users of acetaminophen had an increased risk of stroke and myocardial infarction . Our aim was to explore these results in a geriatric setting . Thus, we conducted a study on a population of 6275 older persons living in nursing homes over an 18‐month period.…”
Section: Incident Strokes At Follow‐up In Regard To Acetaminophen Intmentioning
confidence: 99%